Influence of two different rest interval lengts in resistance training sessions for upper and lower body - Senna, G.; Salles, B. F.; Prestes, J.; Mello, R. A.; Simao, R. (Journal of Sports Science & Medicine, 2009)
Rest intervals between sets appear to be an important variable that can directly affect training volume and fatigue. The purpose of the present study was to compare the influence of two and five-minute rest intervals on the number of repetitions per set, per exercise and total repetitions in resistance training sessions. Fourteen trained men (23.0 ± 2. 2 yrs; 74.9 ± 4.1 kg; 1.75 ± 0.03 m) completed three sets per exercise, with 10RM load in four training sessions. Two sessions involved lower body exercises (leg press, leg extension and leg curl), with two-minute (SEQA) and with five-minute interval (SEQB). The other two sessions involved upper body exercises (bench press, pec-deck and triceps pulley), with two (SEQC) and five-minute intervals (SEQD). For two-minute, five of six exercises presented reductions in the second set, compared with the first set, and for the third set compared with the first and second sets. For five-minute, three of the six exercises presented reductions in the third set, compared with the first sets, and two of the six for the third set, compared with the second sets. The total number of repetitions in SEQA (66.7 ± 4.9) was significantly smaller than in SEQB (80.9 ± 6.9). Similarly, the total repetitions was significantly lower in SEQC (71.1 ± 4.7) compared with SEQD (83.7 ± 6.1). The results indicate that the training session performance is reduced by shorter intervals, being the initial exercises less affected during the progression of the sets.